Mycotoxin toxicity and residue in animal products: Prevalence, consumer exposure and reduction strategies – A review. (15th April 2020) - Adegbeye, Moyosore Joseph; Reddy, Poonooru Ravi Kanth; Chilaka, Cynthia Adaku; Balogun, Olalekan Blessing; Elghandour, Mona M.M.Y.; Rivas-Caceres, Raymundo Rene; Salem, Abdelfattah Z.M.
Abstract: Mycotoxin residues are transferred from feed to animal products, yet, less attention has been paid to it in developing countries. There is a need to find alternative alleviation material for reducing the impact of mycotoxin. This review is meant to elucidate different additives that can reduce mycotoxin residue in animal products in the world, especially in developing countries. There is evidence of relationship between mycotoxin residue in breast milk of nursing mothers and mycotoxin exposure through crop and animal product (egg and milk) intake, especially in Asia, Africa, Middle East, Latin America, and some parts of Europe. Younger livestock tends to have more toxin residues in their tissue compared to older ones. Grazing animal are also exposed to mycotoxin intake which corresponds to high level of mycotoxins in their products including meat and milk. This review shows that phytogenic, probiotic, and prebiotic additives can decrease mycotoxin residues in milk, eggs, meat liver and other tissues of livestock. Specifically, bentonites, difructose anhydride III, yeast ( Trichosporon mycotoxinivorans ), Bacillus spp., or their biodegradable products can reduce mycotoxin residue in animal products. In addition, Ally isothiocyanates from mustard seed were able to mitigate mycotoxins in silo-simulated system. Evidence shows that there are now low-cost, accessible, and eco-friendly additives, which could alleviate the effect of mycotoxin in feed and food. In addition, there is need for aggressive public awareness and farmers' education on the prevalence, and danger caused by mycotoxins, as well as detoxification strategies that can reduce toxin absorption into animal products. Graphical abstract: Image 1